Induksi Kalus serta Regenerasi Tunas dan Akar Cabai melalui Kultur In Vitro - Manzila, Ifa; Hidayat, Sri H; Mariska, Ika; Sujiprihati, Sriani (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2010)
Callus Induction and Regeneration of Shoot and Root ofChill through In Vitro Culture. Ifa Manzila, Sri H.Hidayat, Ika Mariska, and Sriani Sujiprihati. In vitroculture is one way for a fast and effective plant propagation.This method is also useful for preliminary selection of plantresistance to disease, including the chili. In vitro propagationmethod for chili has not been widely reported. A study wasconducted to obtain effective techniques for callus inductionand regeneration into shoots on three red chili cultivars (cv)Gelora, Sudra, and Chili 109. The study consisted of fouractivities, namely the induction of callus formation,induction of embryogenic callus, callus regeneration intoadventitious shoots, and root induction from the adventitiousshoots. Murashige Skoog (MS) medium + 0.6% agar + 3%sucrose were used as basal medium, 20 ml/bottle. Youngleaves, hypocotyls and root tips of 21-day-old chili seedlingswere used as sources of explants. Each experiment wasarranged in a completely randomized design with 10replications, one culture bottle for each treatment. Thecallus induction experiments using the explants of youngleaf explants, hypocotyl, and root tips were done separately.Each treatment consisted of explants from the three chilicultivars on MS medium containing three composition ofgrowth regulators (PGR) BAP + NAA, 10 explants/bottle. Theembryogenic callus induction was conducted by growingthe callus in bottles containing a medium that contains threecompositions PGR 2,4-D + thidiazuron 0.5 mg/l. Induction ofshoot formation was done by growing the embryogeniccallus on medium containing three composition of plantgrowth regulator BAP + NAA. Induction of root formationwas performed by growing adventitious shoots on ½ MS and1 MS medium + NAA 0.5 to 1.0 mg/l. The results showed thatyoung leaves are the best explant source for callus andshoot formations in chili through tissue culture comparedwith the hypocotyl and the tip. Gelora is the most responsivechili cultivar to callus, shoots, and roots formation of in theirrespective medium, compared to Sudra and Chile 109. MSmedium containing BAP 3-7 mg/ml and NAA 1 mg/ml can beused to induce the growth of callus from young leafexplants, hypocotyl and seedling root tip chili cv Gelora,Sudra, and Chile 109, but its growth was very slow and didnot produce embryogenic callus. Embryogenic callusformation can be induced by both non-embryogenic callusHak Cipta © 2010, BB-Biogengrowing the callus on MS medium containing 2,4-D 3 mg/l +thidiazuron 0.5 mg/ l. Formation of callus that can regenerateinto shoots should use an MS medium containing 2,4-D 3mg/l + thidiazuron 0.5 mg/ l followed by subculture on MSmedium + BAP 3 mg/l + thidiazuron 0.5 mg/l to induceshoot elongation. Medium ½ MS and 1 MS containing NAA0.5-1.0 mg/l can be used to induce root formations on shootculture of chili cv Gelora but not for cv Chili 109.